2018
DOI: 10.1093/mnras/sty2297
|View full text |Cite
|
Sign up to set email alerts
|

On the AGB stars of M 4: a robust disagreement between spectroscopic observations and theory

Abstract: Several recent spectroscopic investigations have presented conflicting results on the existence of Na-rich asymptotic giant branch (AGB) stars in the Galactic globular cluster M 4 (NGC 6121). The studies disagree on whether or not Na-rich red giant branch (RGB) stars evolve to the AGB. For a sample of previously published HER-MES/AAT AGB and RGB stellar spectra we present a re-analysis of O, Na, and Fe abundances, and a new analysis of Mg and Al abundances; we also present CN band strengths for this sample, de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…: < δA(Na)> = -0.01 ± 0.04; with results from the infrared study by de Laverny & Recio-Blanco (2013a): < δA(Na)> = +0.11 ± 0.11 and with results fromMacLean et al (2018): < δA(Na)> = +0.04 ± 0.13. Our sodium abundances for ω Centauri are in agreement with the optical highresolution study bySmith et al (2000) having an average difference of < δA(Na)> = 0.03 ± 0.06.…”
supporting
confidence: 72%
“…: < δA(Na)> = -0.01 ± 0.04; with results from the infrared study by de Laverny & Recio-Blanco (2013a): < δA(Na)> = +0.11 ± 0.11 and with results fromMacLean et al (2018): < δA(Na)> = +0.04 ± 0.13. Our sodium abundances for ω Centauri are in agreement with the optical highresolution study bySmith et al (2000) having an average difference of < δA(Na)> = 0.03 ± 0.06.…”
supporting
confidence: 72%
“…As noted in Section 3, 6...376 is an asymptotic giant branch (AGB) star. There has been much discussion in the literature about differences in the abundances of stars on the AGB versus those on the RGB in globular clusters (Norris et al 1981;Campbell et al 2013Campbell et al , 2017MacLean et al 2016MacLean et al , 2018, in particular with respect to apparent differences in their derived metallicities and light element abundances (Lapenna et al 2016;Mucciarelli et al 2019). There are two related effects that are causing these discrepancies.…”
Section: Abundances On the Asymptotic Giant Branchmentioning
confidence: 99%
“…Another still debated case is M4, for which the chemical analyses by MacLean et al (2016) and MacLean et al (2018) suggest a clear lack of 1P stars along the AGB (at variance with the RGB), while opposite results have been obtained by Lardo et al (2017), who found a comparable broadening of AGB and RGB sequences using the C UBI index sensitive to the light element abundances, and by Marino et al (2017), who detected the Na-O anticorrelation among the AGB stars using UVES-FLAMES spectra.…”
Section: Introductionmentioning
confidence: 95%